The career paths less (or more) traveled : a sequence analysis of IT career histories, mobility patterns, and career success - Slaughter, Sandra A. (2013)
This paper examines the objective career histories, mobility patterns, and career success of 500 individuals drawn from the National Longitudinal Survey of Youth (NLSY79), who had worked in the information technology workforce. Sequence analysis of career histories shows that careers of the IT workforce are more diverse than the traditional view of a dual IT career path (technical versus managerial). This study reveals a new career typology comprising three broad, distinct paths: IT careers; professional labor market (PLM) careers; and secondary labor market (SLM) careers. Of the 500 individuals in the IT workforce, 173 individuals pursued IT careers while the remaining 327 individuals left IT for other high-status non-IT professional jobs in PLM or lower-status, non-IT jobs in SLM careers. Findings from this study contribute to refining the concept of "boundaryless" careers. By tracing the diverse trajectories of career mobility, we enrich our understanding of how individuals construct boundaryless careers that span not only organizational but also occupational boundaries. Career success did not differ in terms of average pay for individuals in IT and PLM careers. By contrast, individuals in SLM careers attained the lowest pay. We conclude this study with implications for future research and for the management of IT professionals' careers.